Semantic Field "Catasprophe" in Alternative Worldviews: A Quantitative Dimension - Колесник, Олександр (Studia Philologica, 2024)
The paper addresses language units that constitute semantic space "catastrophe" within alternative English-mediated worldviews. Designation units synonymic or contextually related to catastrophe / disaster, were chosen from the Web 2021 (enTenTen21) corpus suggested by the Sketch Engine and from the custom corpus of present-day rock lyrics processed via the Ant.Conc 3.5.8 tools. The content of the respective concept is considered through the prism of a logical model that addresses an entropic irrevocable transformation of an open system. He paper focuses on the comparative analysis of the space's composition in two worldview variants. The structure of the semantic space is identified as a field, i.e. a dynamic volumetric continuum that sports multi-level organization as well as each level's zonal segmentation. Special attention is paid to functional-semantic and semiotic properties of the space-field's components. The article employs an interdisciplinary approach that encompasses the myth-oriented semiosis theory and broad inter-systemic analogies ("M-logic"). Key words: system, alternative world, semantic space, corpus, myth Стаття розглядає мовні одиниці, які складають семантичний простір "катастрофа" у структурі альтернативних картин світів, актуалізованих засобами англійської мови. Номінативні одиниці, синонімічні або контекстуально пов’язані з "катастрофою", були відібрані з корпусу Web 2021 (enTenTen21), запропонованого Sketch Engine, та з користувацького корпусу сучасних рок-пісень, оброблених за допомогою інструментів Ant.Conc 3.5.8. Зміст відповідного поняття розглядається крізь призму логічної моделі, яка стосується ентропійної безповоротної трансформації відкритої системи, що призводить до її зламу. У статті здійснено порівняльний аналіз композиції простору у двох варіантах картини світу. Структура семантичного простору ідентифікується як поле, тобто динамічний об’ємний континуум, який має багаторівневу організацію, а також зональну сегментацію кожного рівня. Особливу увагу приділено функціонально-семантичним і семіотичним властивостям компонентів простору-поля. У статті використано міждисциплінарний підхід, який охоплює міфоорієнтовану теорію семіозису та широкі міжсистемні аналогії («М-логіка»). Ключові слова: система, альтернативний світ, семантичний простір, корпус, міф